Con gli occhi velati. Note sull’intravedere a partire da W.G. Sebald - David Watkins (Between, 2022)
In Sebald, defects of sight, a recurring feature of his characters, open up the possibility of a new perspective, in which both the concept of ‘estrangement’ and that of ‘disturbing’ come together. With a constantly disoriented gaze which renders unrecognizable what is most familiar, with veiled eyes that make borders and contours imperceptible, Sebald’s characters are able to glimpse the continuity between different forms of life, and to perceive the peculiar way in which the dead coexist beside the living. The aim of this article is to examine the meanings of Sebald’s ‘blurred visions’, with special focus on the ateliers and the moments of pictorial creation described in his works.